2019
DOI: 10.1021/acsnano.9b04685
|View full text |Cite
|
Sign up to set email alerts
|

Nanophotonic Cell Lysis and Polymerase Chain Reaction with Gravity-Driven Cell Enrichment for Rapid Detection of Pathogens

Abstract: Rapid and precise detection of pathogens is a critical step in the prevention and identification of emergencies related to health and biosafety as well as the clinical management of community-acquired urinary tract infections or sexually transmitted diseases. However, a conventional culture-based pathogen diagnostic method is time-consuming, permitting physicians to use antibiotics without ample clinical data. Here, we present a nanophotonic Light-driven Integrated cell lysis and polymerase chain reaction (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 39 publications
0
61
0
Order By: Relevance
“…Thanks to the larger contact area between heater and solution, lower heat capacity and high efficiency of light‐to‐heat conversion, photothermal PCR can achieve ultrafast thermocycling with the heating and cooling rates of 16.6 and 9.4 °C s −1 , respectively. [ 134 ] The 40 thermal cycles can be accomplished in 5–10 min, [ 138 ] whereas it takes about 2 h for common PCR. Inspired by fluorescence signal enhancement of photonic particles (PCs) (Figure 9b), photonic‐enhanced NAAR were developed in combination of PCs with traditional NAAR, in which PCs serve as the substrate to maximize the emission signals of fluorescein in reaction mixture by slow‐photon effect.…”
Section: Other Methods With Opticsmentioning
confidence: 99%
“…Thanks to the larger contact area between heater and solution, lower heat capacity and high efficiency of light‐to‐heat conversion, photothermal PCR can achieve ultrafast thermocycling with the heating and cooling rates of 16.6 and 9.4 °C s −1 , respectively. [ 134 ] The 40 thermal cycles can be accomplished in 5–10 min, [ 138 ] whereas it takes about 2 h for common PCR. Inspired by fluorescence signal enhancement of photonic particles (PCs) (Figure 9b), photonic‐enhanced NAAR were developed in combination of PCs with traditional NAAR, in which PCs serve as the substrate to maximize the emission signals of fluorescein in reaction mixture by slow‐photon effect.…”
Section: Other Methods With Opticsmentioning
confidence: 99%
“…As a result of this, biochemical and molecular assays remain the gold standard methods of diagnosis for certain infectious diseases and one of the primary focuses in POCT [ 32 , 70 , 77 , 105 , 106 ]. Consequently, much research over the past decade has been devoted to streamlining and improving the sample preparation required for these methods so that it can be performed more easily in POC and low-resource settings (LRS) for lower costs and with adequate analytical sensitivity and short turnaround time [ 105 , 106 , 107 ]. Within this research area, several trends have been observed, including chip or cartridge systems with integrated sample preparation [ 32 , 105 , 106 , 107 , 108 , 109 , 110 ] and portable or simplified systems for extractions and separations used with biochemical or molecular diagnostic techniques [ 111 , 112 , 113 ].…”
Section: Integrated and Portable Sample Preparation Devicesmentioning
confidence: 99%
“…One of the main limitations to their use is the need for simple and quick extraction and separation of analytical targets from clinical samples and the need for complex laboratory equipment such as a thermocycler in order to carry out the amplification process [ 26 , 37 , 67 , 74 ]. To overcome this, one approach has been to design systems with integrated sample preparation and detection, commonly called “molecular cartridge-based” or “chip-based” tests that allow for clinical samples to be analyzed with minimal equipment requirements [ 27 , 74 , 107 , 108 ]. As shown by the example in Figure 6 , this approach often utilizes specifically designed materials for the extraction, separation, and amplification steps of the NAAT sample preparation process and portable equipment such as LED lasers and smartphones for the detection and quantification steps [ 107 ].…”
Section: Integrated and Portable Sample Preparation Devicesmentioning
confidence: 99%
“…[ 15 , 16 , 17 ]. Especially, stimuli-sensitive nanoparticles have been spotlighted for the last two decades since stimuli-sensitive drug delivery to specific sites of the body enables conventional drugs to target diseased cells or tissues with some response to a stimulus [ 18 , 19 , 20 , 21 ]. For example, nanoparticles composed of hyaluronic acid and poly(L-histidine) copolymer having disulfide linkages respond to the acidic pH/redox potential of tumors and then deliver anticancer drugs against tumors in a site-specific manner [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, nanoparticles composed of hyaluronic acid and poly(L-histidine) copolymer having disulfide linkages respond to the acidic pH/redox potential of tumors and then deliver anticancer drugs against tumors in a site-specific manner [ 19 ]. Stimuli-sensitive nanoparticles efficiently deliver CIP in an on-demand manner in infectious microenvironment models in vivo and thus show improved therapeutic efficacy compared to free CIP [ 21 , 22 , 23 ]. Alomary and Ansary reported that proanthocyanin-capped biogenic TiO 2 nanoparticles showed inhibitory behavior against biofilm formation through ROS generation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%